Joint Study on Western Ghats Development Programme in Maharashtra Design, Instruments, Instructions, etc. - Planning Commission (Planning Commission, 1993)
The need to conserve natural resources and the environment, particularly to prevent further damange to the fragile and irreplceable eco-system, was recognised by the Government of India, long back. In this back drop the Hill Areas of the country, particularly the Himalayan and the Western Ghats regions, have been recognised as areas in need of special attention.
Directorate of Economics and Statistics (Government of Maharashtra)